Leslee Udwin's India's Daughter (2015), the power of storytelling and question of social change in the #MeToo era. (1st June 2021) - Shrivastava, Nidhi
In an op-ed, Leslee Udwin, the filmmaker of the controversial but meaningful documentary, India's Daughter speaks of the tensions she faced in India amidst her film's release. After her movie was banned in India, she abruptly left the country to avoid arrest. Her film explores the complexities and nuances of the 2012 Delhi rape case. It drew criticism when the trailer was released because it allegedly focused on the rapist's narrative. Drawing upon my interview with Udwin and archival research, I explore the multitude of ways in which Leslee's position as a powerful storyteller and an outsider influenced her documentary's success within and outside of India. A medium of social change, Udwin's documentary underscores the patriarchal and misogynistic attitudes that continue to exist while simultaneously challenging the role of the state, politicians and law enforcement who are in charge of protecting women's rights.